"You reap what you pick". Issue 2 (2014) - Ram A. Cnaan; Ganesh Bhat; Lucas C.P.M. Meijs; Femida Handy
<x xml:space="preserve"> Abstract </x> Purpose – This article aims to examine the history, mechanisms, interconnectedness and effectiveness of the jasmine‐growing enterprise in coastal Karnataka. This article investigates the formation and ongoing successful operation of a community enterprise that is locally originated and administered. The case of the jasmine flower growers in coastal Karnataka is a case of small‐scale growers who for 75 years have operated a long‐standing local community‐based enterprise. Using trust, repeated interactions and efficient mechanisms of pricing and distribution, this enterprise has prevented poverty among its participants for three generations. Design/methodology/approach – This article provides a descriptive analysis of the enterprise as well as results from an empirical study of 700 growers. The article used cluster analysis of local villages to represent the 7, 000 participating households. Findings – Studying local growers who are the producers of the flowers and who are living off of it, this article found a high level of satisfaction and trust towards those running the enterprise. For many people in the region, this ongoing enterprise is the difference between poverty and hunger and living well. Research limitations/implications – The article is based on one local community that is lucky to have a desired resource (one type of jasmine flower) coveted by many users. Practical implications – Combined, this article provides an account of a unique and successful sustainable enterprise, initiated and run at the grassroots level, which serves as a model for future economic development. In addition, it lists the features that are most relevant for the ongoing success of the enterprise and suggests how a new social and economic development project can learn from this enterprise. Originality/value – This is an amazing enterprise that was not studied before and can be a role model for many adaptations. <ack> <x xml:space="preserve"> Acknowledgements </x> Acknowledgement The authors wish to thank the many Karnataka growers who so graciously took time to answer our questionnaire and showed us hospitality and compassion. We also are very grateful to Ms Valentina Raman for her expert editing. </ack>